2017
DOI: 10.1186/s13071-017-2252-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal survey on the distribution of Biomphalaria sudanica and B. choanomophala in Mwanza region, on the shores of Lake Victoria, Tanzania: implications for schistosomiasis transmission and control

Abstract: BackgroundSchistosomiasis is hyper-endemic in the Lake Victoria basin; with intestinal schistosomiasis plaguing communities adjacent to the lake, where the intermediate host snails live. The two intermediate host species of Schistosoma mansoni in the Mwanza region are Biomphalaria sudanica, found on the banks of the lakes, and B. choanomphala, found in the lake itself. There are few longitudinal surveys documenting changing abundance and differential transmission patterns of these Biomphalaria snails across se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 21 publications
3
38
4
Order By: Relevance
“…11,22 Gouvras et al, found B. choanomphala to be focally distributed in the Tanzanian waters of the lake, including in some more protected inlets. 34 They noted, as did we, a general trend for this species to be more common in western than eastern locations, and considered a possible gradual change in substratum conditions from west to east might be responsible. Many other factors such as levels of dissolved oxygen, pollution and seasonal effects like rainfall may also influence B. choanomphala populations.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…11,22 Gouvras et al, found B. choanomphala to be focally distributed in the Tanzanian waters of the lake, including in some more protected inlets. 34 They noted, as did we, a general trend for this species to be more common in western than eastern locations, and considered a possible gradual change in substratum conditions from west to east might be responsible. Many other factors such as levels of dissolved oxygen, pollution and seasonal effects like rainfall may also influence B. choanomphala populations.…”
Section: Discussionsupporting
confidence: 70%
“…Many other factors such as levels of dissolved oxygen, pollution and seasonal effects like rainfall may also influence B. choanomphala populations. 33,34 We did not observe any association between the abundance of B. choanomphala and water hyacinths. Although hyacinth mats can cover areas of the lake where deeper water and hence B. choanomphala populations are present and could have adverse shading or other effects, our impression was that hyacinth mats along the more exposed shores away from the Gulf were more prone to be dispersed by winds.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations